Analysis and Documentation of Requirements for the Software Package for Conducting Computational Experiments and Numerical Investigation “Flow Tube – Liquid” System of a Coriolis Flow Meter - Gudkova, E.A. (Modelling and Data Analysis, 2024)
Item. This article describes the stages of development of a software package designed to conduct a series of computational experiments on numerical modeling of the "flow tube - liquid" system of a Coriolis flow meter and automation of algorithms for subsequent data processing and visualization. The purpose of this article is to formulate and document the requirements for a software package, and its design based on modern approaches to the development of software products. Methods. The structure of requirements for the software package was developed based on the Software Requirements Specification template adopted in the Rational Unified Process software development methodology, in accordance with the classification of requirements for FURPS+ software systems. Python 3 and the interpreted programming language of the MATLAB environment were used to develop the complex routines. Results. A structure of requirements for the software package has been developed, including functional and non-functional requirements. A software package consisting of three subprograms has been developed, its structure, main components and capabilities are described, and examples of use are demonstrated. Conclusions. The software package solves the problems of automating modeling algorithms, processing and visualizing data obtained as a result of experiments. It can be used in engineering and scientific research related to the analysis of the performance of Coriolis flow meters. Предмет. Работа описывает этапы разработки программного комплекса, предназначенного для проведения серий вычислительных экспериментов по численному моделированию системы «расходомерная трубка - жидкость» кориолисова расходомера и автоматизации алгоритмов последующей обработки и визуализации данных. Цель данной статьи заключается в формировании и документировании требований к программному комплексу, и его проектированию на основе современных подходов к разработке программных продуктов. Методы. Структура требований для программного комплекса разработана на основе шаблона Software Requirements Specification, принятого в методологии разработки программного обеспечения Rational Unified Process, в соответствии с классификацией требований к программным системам FURPS+. Для разработки подпрограмм комплекса использованы язык Python 3 и интерпретируемый язык программирования среды MATLAB. Результаты. Разработана структура требований для программного комплекса, включая функциональные и нефункциональные требования. Разработан программный комплекс, состоящий из трех подпрограмм, описаны его структура, основные компоненты и возможности, продемонстрированы примеры использования. Выводы. Программный комплекс решает задачи автоматизации алгоритмов моделирования, обработки и визуализации данных, полученных в результате экспериментов. Он может быть использован в инженерных и научных исследованиях, связанных с анализом работы кориолисовых расходомеров.